Effects of Evolving Gender Roles on Women’s Economy: Highlighting the Female Experience Through Painting. - Ankunda, Mark (Kabale University, 2025)
This study explored the impact of shifting gender roles on women’s economic status, aiming to raise awareness about the female experience in Kabale District, with a focus on women’s growing participation in income-generating activities. It sought to examine the factors driving these changes, the challenges women encounter in achieving economic empowerment, and the effects of their involvement on household dynamics and community development. Using a qualitative data collection approach, the study offered a detailed understanding of the evolving gender roles in Kabale District and contributed to discussions on gender equality and economic progress. The findings would provide valuable insights for policymakers, development practitioners, and local communities striving to advance women’s economic rights and promote equity within family structures.